Disease-driven engineering of peptide-targeted DM1 loaded liposomal nanoparticles for enhanced efficacy in treating multiple myeloma by exploring DM1 prodrug chemistry. (January 2023) - Khan, Sabrina; Mejia, Franklin; Shin, Jaeho; Hwang, Gyoyeon; Omstead, David T.; Wu, Junmin; Cole, Sara L.; Littlepage, Laurie E.; Bilgicer, Basar
Abstract: Here, we report a CD138 receptor targeting liposomal formulation (TNP[Prodrug-4]) that achieved efficacious tumor growth inhibition in treating multiple myeloma by overcoming the dose limiting severe toxicity issues of a highly potent drug, Mertansine (DM1). Despite the promising potential to treat various cancers, due to poor solubility and pharmacokinetic profile, DM1's translation to the clinic has been unsatisfactory. We hypothesized that the optimal prodrug chemistry would promote efficient loading of the prodrug into targeted nanoparticles and achieve controlled release following endocytosis by the cancer cells, consequently, accomplish the most potent tumor growth inhibition. We evaluated four functional linker chemistries for synthesizing DM1-Prodrug molecules and evaluated their stability and cancer cell toxicity in vitro . It was determined that the phosphodiester moiety, as part of nanoparticle formulations, demonstrated most favorable characteristics with an IC50 of ∼16 nM. Nanoparticle formulations of Prodrug-4 enabled its administration at 8-fold higher dosage of equivalent free drug while remaining below maximum tolerated dose. Importantly, TNP[Prodrug-4] achieved near complete inhibition of tumor growth (∼99% by day 10) compared to control, without displaying noticeable systemic toxicity. TNP[Prodrug-4] promises a formulation that could potentially make DM1 treatment available for wider clinical applications with a long-term goal for better patient outcomes. Graphical abstract: Image 1 Highlights: Nanoparticle formulation of DM1-Prodrug surpassed the free drug by enhancing its safety profile and therapeutic window. Engineered targeted nanoparticles outperformed non-targeted particles with a superior efficacy (∼99%) in vivo . Developed formulation enabled delivery of higher dosage (8-fold) of equivalent free drug by solving both solubility & systemic toxicity issues.